Characterization of the cleaved edge cross section of the heterostructures with GaMnAs layer by the confocal micro-Raman spectroscopy. (February 2017) - Kudrin, A.V.; Plankina, S.M.; Vikhrova, O.V.; Nezhdanov, A.V.; Mashin, A.I.; Drozdov, Yu.N.; Shvetsov, A.V.
Highlights: The cross section of sub-micron thick heterostructures was investigated by the micro-Raman spectroscopy (MRS). The shift of a TO mode position in top GaMnAs layers associated with elastic strains was observed. The MRS is appropriate for the analysis of heterostructures with the thickness comparable to an analyzing laser spot size. Abstract: Confocal micro-Raman spectroscopy was used to measure cross-section linescans of the cleaved edge of heterostructures involving a GaMnAs layer. The investigations revealed a shift of the TO mode in the compressed GaMnAs layer to high frequencies relative to the TO GaAs mode in the substrate and to low frequencies in the tensile GaMnAs layers. These results are in agreement with the different manifestations of the anomalous Hall effect in the GaMnAs layers, with either compressive or tensile strains. It is shown that Raman spectroscopy is an appropriate method for the investigation of cross-sectional semiconductor heterostructures whose total thickness is comparable to the size of the analyzing laser spot.